Complex cellular structure evolution of polystyrene/poly (ethylene terephthalate glycol-modified) foam using a two-step depressurization batch foaming process. (November 2016) - Wang, Xiangdong; Wang, Wenzhao; Liu, Bengang; Du, Zhongjie; Peng, Xiangfang
In order to decrease the cell size and maintain very high volume expansion ratio simultaneously, a methodology for the preparation of complex cellular structure (CCS) in polystyrene/poly(ethylene terephthalate glycol-modified) (PS/PETG) blend using two-step depressurization pressure batch foaming process was proposed. First, the optimum foaming temperature for PS and PS/PETG blend, respectively, were confirmed by one-step depressurization foaming process. Then, the CCS in PS and PS/PETG blending foam were fabricated by two-step depressurization foaming process at the optimum foaming temperature. The rheological properties of PS and PS/PETG blend were tested by dynamic rotational rheometer. The dispersion morphologies and foam morphologies were observed by scanning electron microscope. The lowest densities of PS and PS/PETG blending foams were obtained at the temperature of 136℃. The interfaces between PS and PETG could act as nucleation sites for the cell nucleation, which were helpful to fabricate the CCS. The CCS could be controlled by tuning the degree of the first-step depressurization and the holding time. The results showed that the large cells could be beneficial to decrease the foam density and the presence of small cells was beneficial to increase the cell number.